I'm a born liar a Fellini lexicon - Pettigrew, Damian (Harry N. Abrams, Inc., 2003)
"I'm a Born Liar: A Fellini Lexicon, based on a candid and revealing series of interviews with Federico Fellini conducted in 1992, the year before his death, offers rare insight into the inventive and original world of one of the greatest filmmakers of all time. Fellini, who directed a host of legendary films, including 8 1/2, La Strada, La Dolce Vita, Satyricon, Amarcord, and Nights of Cabiria, is an exuberant storyteller with an untamed imagination, and these interviews, which also form the backbone of the documentary Fellini: I'm a Born Liar, capture the energy and passion of its subject."